Community-Based Correction Implementation Analysis (Global Survey) - hamja; Al Ghifari, Bintang Azhar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Community-based corrections has become an alternative approach in the criminal justice system to address the challenges arising from the conventional incarceration approach. This approach not only aims to rehabilitate offenders through social integration, but also reduces recidivism rates and prison overcrowding. However, its implementation faces various obstacles, including complex legal issues, such as differences in regulatory interpretation, policy gaps between countries, and limited legal resources. This study aims to analyze the implementation of community-based corrections from a legal perspective using a global survey. The research methodology includes data collection from various countries to identify legal challenges, best practices, and innovations in the community-based corrections system. The results show that the success of the implementation of this approach is greatly influenced by the existing legal framework, policy support, and community engagement. This abstract provides insight into the importance of a holistic approach involving updating the legal framework, improving coordination between institutions, and strengthening community capacity to support the sustainability of community-based corrections. This global survey also recommends more inclusive and adaptive policies to address differences in legal contexts across jurisdictions.